Online argumentation-based learning aided by digital concept mapping during COVID-19: implications for health management teaching and learning. Issue 1 (6th August 2021) - Alt, Dorit; Naamati-Schneider, Lior
Abstract : Purpose: The COVID-19 pandemic has affected educational systems worldwide, forcing them to abruptly shift from face-to-face to online teaching and learning. This case study illustrates how a traditional lecture-based activity for undergraduate students in a Management of Health Service Organizations program was transformed into an argumentation-based learning activity using the technique of digital concept mapping and was deployed in an online format during the COVID-19 lockdown. Design/methodology/approach: The students were tasked with solving an ill-structured problem bearing significance for their future professional lives and connected to the contents of their course (entitled "Assimilation of service quality in health systems"). The activity was composed of two phases. In Phase 1, participants were asked to provide five arguments to establish their proposed solution to the problem by using a concept map on a digital platform (Mindomo). In Phase 2, they were asked to substantiate their arguments. Reflective journals were used to ascertain how the participants viewed the activity. Thematic analysis was used to analyze the qualitative data by searching for themes demonstrating different epistemological positions. Findings: Six themes were inductively derived from the students' reflections: (1) transitioning from passive to active learning; (2) generating epistemic change; (3) social perspective-taking; (4) domain-based knowledge; (5) prior knowledge and experience; and (6) online collaboration with other students. Episodes, thoughts and feelings expressed by the students were reported so as to increase the reliability of the recurrent and common themes. Originality/value: This study mainly shows that combining constructivist teaching and learning tools with advanced technology in an online course enables the development of lifelong learning capabilities among students in the health management professions.